Hidróxido de cálcio como aditivo para cana-de-açúcar in natura para alimentação de bovinos - Dias, Alexandre Menezes (2009)
The experiments were carried out in the Dom Bosco Catholic University - UCDB, in Campo Grande, MS, aimed to study the effect of the hydroxide of calcium (Ca(OH)2) in powder mixed with sugar cane. For thermoanalithic study were evaluad four levels, containing 0, 10, 20 and 30 g of hydroxide of calcium per kg of sugar cane. As the level of calcium hydroxide increased it was observed an increase of liberated energy, being of 4.35; 4.84; 5.59 and 5.67 KJ/g for the levels 0, 10, 20 and 30 g/kg, respectively. In the treatment calcium hydroxide + urea there was an increase in the liberated energy, presenting values of 4.35, 5.00, 5.57 and 5.68 KJ/g for the levels 0, 10, 20 and 30 g/kg, respectively. There is a direct relationship between the level of hydroxide in the sugar cane and the thermo decomposition process, as well as an increase in the liberated energy. For determination of the aerobic stability through pH measure it was evaluated the hydrated lime, the urea and its combinations as addictive. (0, 5, 10, 15, 20, 25 and 30 g/kg of natural matter of sugar cane for each addictive tested) and five times of storage (0, 24, 48, 72 and 96 hours after the harvest and application of the addictive). For the DM in situ degradability there were evaluated the addition of 10 g/kg or not of calcium hydroxide in the sugar cane in the times 0, 24, 48 and 72 hours after mixture. The sugar cane without hydroxide presented a higher soluble fraction (fraction a). The hydrated lime had positive effect in the degradable potential fraction (fraction b) and in the degradation rate (fraction c). It was determined the chemical composition and the digestibility in vitro of the dry matter (IVDMD), of the neutral detergent fiber (IVNDFD) and of the acid detergent fiber (IVADFD) of the sugar cane with levels of hydroxide. The treatments considered the inclusion of calcium hydroxide in the levels of 0, 8, 16 and 24 g/kg of sugar cane. The amounts of DM and ashes had linear increases while the OM decreased linearly when it increases the level of calcium hydrated. The level of calcium hydroxide promoted reduction in the amounts of NDF, ADF (37.78; 32.27; 29.34 and 29.01%) and NFC. The inclusion of lime showed increases in the amounts of hemicellulose being of 11.14; 15.39; 16.85 and 17.66% and 16.48 for the levels of 0, 8, 16 and 24g/kg, respectively. There was a quadratic effect for IVDMD, IVNDFD and IVADFD of the sugar cane. For evaluation of the nutrients intake, nutrients apparent digestibility, ruminating parameters and the ingestible behavior was used four cows body weight (BW) medium of 412.04 kg ± 37.3 kg, distributed in a latin square 4x4, with four periods of 21 days, being 14 for adaptation and seven for data collection. The treatments used the inclusion of calcium hydroxide in the levels of 0, 8, 16 and 24 g/kg of sugar cane in the supplied natural matter. For the ruminating parameters were used crops of liquid ruminal, for determination of the pH and N-NH3 before (time zero) and 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 and 12 hours after the supply of the diet and to determine the concentration of VFA at 0, 3, 6, 9 and 12 hours. There was a quadratic effect for the intake of nutrients, and the intake of ADF presented linear effect. The digestibility coefficients presented quadratic effect for the levels of calcium hydroxide inclusion. For rumination and total leisure activities, there was no effect of the level. The total time of chewing, number of bolus ruminal and time for rumination of each bolus had a significant effect. There was no effect of calcium hydroxide level on pH and N-NH3of liquid ruminal. There was effect of levels tested for the concentration of VFA. The calcium hydroxide powder mixed to sugar cane, has the effect of fiber fraction of sugar cane improving their use by encouraging increase in the consumption and digestibility of fibrous fraction of the cell wall.